Color Matching of Universal Shade Resin-Based Composite with Natural Teeth and Its Stability before and after In-Office Bleaching - AlHabdan, AlHanouf; AlShamrani, Ahoud; AlHumaidan, Randa; AlFehaid, AlJohrah; Eisa, Sara (International Journal of Biomaterials, 2022)
Objectives. Esthetics is an essential issue for the long-term success of composite resin restoration. Therefore, this study aimed to view the esthetics of universal shade composite resin restorations and to assess its color matching before and after bleaching. Materials and Methods. Overall, 40 freshly extracted premolars were mounted in an acrylic resin mold, and Class V cavities were then prepared and restored by OMNICHROMA composite (Tokuyama Dental, Tokyo, Japan) and polished with 2-step polishing system. Baseline color analysis was performed using VITA Easyshade V digital spectrophotometer, and another color analysis was carried out 24 hours after storage in distilled water. In-office bleaching was carried out, and color measurements were taken after bleaching and 2 weeks postbleaching. The data were statistically analyzed using SPSS 26.0 Windows version statistical software. Changes were considered statistically significant at P = 0.05. Results. ΔE value of OMNICHROMA restoration before and after restoration was 6.474, 3.529 before and after bleaching, and 3.651 two-weeks postbleaching. In-office bleaching was effective in bleaching the OMNICHROMA specimens as the restoration showed positive ΔL∗ values, which indicated that the specimens were lighter in color after bleaching; however, the bleaching effect was not maintained after 2 weeks. Conclusion. OMNICHROMA universal shade composite resin restoration showed different color matching values with the adjacent enamel of class Vs. The material appeared lighter in shade postbleaching, and the color change was not maintained 2 weeks postbleaching.